Innovative Strategies for Smart Tourism Growth in Zhuhai, China - Nurmalinda, Elda; Rahmanita, Myrza; Tao, Liu Zi (International Journal of Scientific Research and Management (IJSRM), 2025)
Zhuhai, one of China's rapidly developing tourist destinations, embraces smart tourism as a strategic approach to enhance visitor experiences, optimise resource management, and promote sustainable tourism growth. This study explores innovative strategies for implementing smart tourism in Zhuhai by integrating advanced technologies such as big data analytics, the Internet of Things (IoT), and artificial intelligence (AI). The research employs a mixed-methods approach, combining qualitative interviews with stakeholders and quantitative analysis of tourism trends. Key findings highlight the importance of digital infrastructure development, seamless integration of innovative services, and fostering public-private collaborations. Challenges such as data security, stakeholder alignment, and technology adoption are addressed, providing a comprehensive framework for practical, innovative tourism development. This study contributes to the growing knowledge of smart tourism by offering actionable insights and recommendations for Zhuhai’s tourism sector, with potential applications for other emerging smart tourism destinations globally.